Mechanisms of Fetal Programming in Hypertension - John Edward Jones; Julie A. Jurgens; Sarah A. Evans; Riley C. Ennis; Van Anthony M. Villar; Pedro A. Jose (Hindawi Limited, 2012)
Events that occur in the early fetal environment have been linked to long-term health and lifespan consequences in the adult. Intrauterine growth restriction (IUGR), which may occur as a result of nutrient insufficiency, exposure to hormones, or disruptions in placental structure or function, may induce the fetus to alter its developmental program in order to adapt to the new conditions. IUGR may result in a decrease in the expression of genes that are responsible for nephrogenesis as nutrients are rerouted to the development of more essential organs. Fetal survival under these conditions often results in low birth weight and a deficit in nephron endowment, which are associated with hypertension in adults. Interestingly, male IUGR offspring appear to be more severely affected than females, suggesting that sex hormones may be involved. The processes of fetal programming of hypertension are complex, and we are only beginning to understand the underlying mechanisms.